IMPLEMENTASI ASPEK DIGITAL MARKETING PADA INOVASI “e-KATALOG UMKM KECAMATAN PORONG KABUPATEN SIDOARJO” DALAM RANGKA MENDUKUNG PERTUMBUHAN EKONOMI (E-Jurnal Ekonomi Pembangunan, 2025)
This authorship was motivated by the problems of economic development in Sidoarjo Regency during the Covid-19 pandemic, especially those that afflicted MSME actors. The economy in Sidoarjo Regency during the Covid-19 pandemic experienced negative economic growth, regional disparities, and MSME marketing problems. The data used is secondary data. The secondary data was obtained through literature study. The analysis technique used is qualitative descriptive, while the method used is Science and Technology Diffusion. The result of this writing is that Porong District succeeded in creating an innovation "e-Catalog of MSMEs, Porong District, Sidoarjo Regency". This website-based application innovation has various advantages. Therefore, this application is expected to be used in supporting the implementation of data collection, updating data, marketing programs, and problemsolving of existing problems in encouraging regional economic growth in the context of economic recovery after the Covid-19 pandemic. In addition, it also contributes to the achievement of regional priority program targets that have been set in regional development planning documents.
Keywords: Economic Growth; Disparity; MSMEs; Innovation; and Website-Based Applications.